Prevalence and Molecular Characterization of Carbapenem Resistance Genes in Clinical Klebsiella pneumoniae Isolates and Their Therapeutic Implications - Noor Raad Swadi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Carbapenem-resistant Klebsiella pneumoniae represents a major clinical challenge because of its multidrug-resistant nature and limited therapeutic options. The purpose of this study was to identify the major genes of the carbapenemase among clinical K. pneumoniae isolates and assess their relationship with antimicrobial resistance in Baghdad. Among 110 non-duplicate isolates from various clinical specimens, standard microbiological procedures were used to identify the isolates. Antimicrobial susceptibility testing, phenotypic detection of carbapenemase activity, and PCR for blaNDM, blaKPC, blaOXA-48-like, blaVIM and blaIMP were done. Carbapenem resistance was found in 69.1% of the isolates and the presence of carbapenemase genes was detected in 67.3% of the isolates. blaNDM, blaOXA-48-like and blaKPC were the most common gene types. Multidrug resistance and fewer effective drugs were observed among gene-positive isolates. Colistin and tigecycline have the highest activity. These findings emphasize the importance of integrating phenotypic and molecular detection methods to guide appropriate antimicrobial therapy and strengthen infection-control strategies.